Two new species of the subtribe Cyclopogoninae (Orchidaceae) from Guatemala - Archila Morales, Fredy L.; Szlachetko, Dariusz L. (Biodiversity: Research and Conservation, 2013)
Two new species of Guatemalan Cyclopogoninae are described and illustrated; one of them represents the Mesoamerican genus Potosia (Schltr.) R. Gonzalez & Szlach. ex Mytnik, the other - Neotropical Pelexia Poit. ex Rich. They are compared with other Guatemalan members of the genera.